Buccal bone width adjacent to the lower left third molar and loss of Root Pulp Visibility (RPV). (September 2020) - Rachwal, Jessica; Viner, Mark; Andiappan, Manoharan; Roberts, Graham; Lucas, Victoria S
Highlights: Cone Beam Computed Tomography has been used to measure the width of the mandibular bone buccal to lower Third Molars. There is close Left -Right symmetry in the bone buccal to the lower third molars. The loss of visibility of the root pulp of the lower third molars appears related to the thickness of the buccal bone. Abstract: Introduction: .The use of dental panoramic radiographs to assess dental development is hindered by the distortion and artefacts associated with such radiographic exposure techniques. Objective: The purpose of this communication is to explore the feasibility of using CBCT to measure the bone buccal to lower third molars to determine the possible cause of loss of root pulp visibility as visualised on conventional dental panoramic tomographs. Material and Methods: The radiographic archives of The Royal London Hospital were searched for suitable CBCT images. These were examined using Vatech Ewoo CBCT scanner and Pax Reve 3D software. Scans were reformatted into the required parasagittal, axial and coronal sections using SECTRA PACS (Picture Archiving & Communication) software. Measurements of specified parameters were made and the average of these measurements was used to estimate the width of tooth and bone buccal to the pulp that contributed to the loss of Root Pulp Visibility. Results: There was concordance between the measurements for the left and right side for the average measurement of the dentine and bone buccal to the pulp. Conclusions: The dentine and bone buccal to the pulp of the lower third molar roots is symmetrical. Further work is needed to explore the value of this technique to Dental Age Estimation.